1981
DOI: 10.1063/1.329093
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature thermoluminescence studies of Al23

Abstract: Thermoluminescence (TL) and emission spectra studies of single-crystal A1203 have been conducted in the temperature interval 10-300 K. Glow curves resulting from either x or UV radiation at 10 K were recorded and analyzed to yield thermal activation energies (E) and frequency factors (s) associated with each glow peak. A typical glow curve exhibits maxima at 60 K (E = 0.17 eV, s = 5×1012 s−1), 100 K (E = 0.22 eV, s = 8×109 s−1), 220 K (E = 0.56 eV, s = 7×1010 s−1), 260 K (E = 0.72 eV, s = 3×1012 s−1), and 290 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…We agree with this hypothesis for exoelectrons observed at about 230 K [5], which correspond to hole detrapping [5,6,8,9], and for the thermally stimulated peaks at about 60 K [10] and 100 K [5], which are also related to the release of holes [9]. Nevertheless, the case of the 275 K TSEE peak is quite different: this peak is due to electron detrapping [5,6,9] and could be explained by the direct ejection of electrons into the vacuum [5]. The same assumption could be made for peak 440 K which is also due to electron detrapping [8].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…We agree with this hypothesis for exoelectrons observed at about 230 K [5], which correspond to hole detrapping [5,6,8,9], and for the thermally stimulated peaks at about 60 K [10] and 100 K [5], which are also related to the release of holes [9]. Nevertheless, the case of the 275 K TSEE peak is quite different: this peak is due to electron detrapping [5,6,9] and could be explained by the direct ejection of electrons into the vacuum [5]. The same assumption could be made for peak 440 K which is also due to electron detrapping [8].…”
Section: Introductionsupporting
confidence: 89%
“…Most of the works [6,7] devoted to the study of the TSEE mechanisms of α-alumina conclude that TSEE is governed by an Auger-like mechanism. We agree with this hypothesis for exoelectrons observed at about 230 K [5], which correspond to hole detrapping [5,6,8,9], and for the thermally stimulated peaks at about 60 K [10] and 100 K [5], which are also related to the release of holes [9]. Nevertheless, the case of the 275 K TSEE peak is quite different: this peak is due to electron detrapping [5,6,9] and could be explained by the direct ejection of electrons into the vacuum [5].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Cook et al [7] studied low-temperature TL (ltTL) of Al 2 O 3 in the range 10 to 300 K, using X-ray and UV irradiation, and observed 60 K (E=0.17 eV), 100 K (E=0.22 eV), and 220 K (E=0.56 eV) peaks that arise from thermal release of trapped holes from F-type centers. In addition, 260 K (E=0.72 eV) and 290 K peaks attributed to thermal-released electrons from F + -type centers are also observed.…”
Section: Tl Process Analysis and Kinetic Modelmentioning
confidence: 99%
“…Much work [6][7][8][9] has been done to study the TL properties of Al 2 O 3 crystals in the range 90-500 K. These studies have shown that TL peaks at 60, 100, 220, 260, and 290 K were associated with F-type centers and 435 K peak was attributed to V-type centers. Little work has been done though on the TL properties of Al 2 O 3 crystals grown in a reducing atmosphere.…”
mentioning
confidence: 99%